Pengaruh Teknik Sterilisasi dan Komposisi Medium terhadap Pertumbuhan Tunas Eksplan Sirsak Ratu - Sulistiyo, Rico Hutama; Luthfiyyah, Zayyan; Susilo, Buana; Dalimartha, Lengga Nurullah; Wiguna, Eko Chandra; Yuliana, Nuniek; Prasetyo, Endry Nugroho (Bioedukasi: Jurnal Pendidikan Biologi, 2018)
Successful tissue culture of soursop plants requires proper sterilization techniques and hormone levels to produce good shoot growth. This study aims to determine the effect of sterilization techniques and medium composition of soursop explants, using factorial completely randomized design with 2 factors: sterilizing agents and medium composition, repeated 3 times. Hydrogen Peroxide, Mercury and Sodium Hypoclorite used as sterilizing agents. The medium composition used in this study consisted of 3 levels: MS 0, MS 0.5 ppm BAP + 0.05 ppm NAA and MS 1 ppm BAP + 0.1 ppm NAA. The best treatment is MS medium 0.5 ppm BAP + 0.05 ppm NAA with hydrogen peroxide sterilizing agent which produces the highest propagation level and lowest contamination level.